GENDER AND SEXUALITY UNDER THE ARCHEGENEALOGICAL ANALYSIS OF KNOWLEDGE – POWER - de Toni Junior, Claudio Noel [UNESP] (Universidade Federal da Bahia, 2024)
Through through readings of the works of French philosophers such as Bourdieu and Foucault. Foucault, they discuss the classics cited as a way of perceiving social, economic and gender social, economic and gender inequalities in capitalist societies on forms of domination. Male domination in the works of Bourdieu, of economic capital that generates inequalities in which many people hold most of the wealth between nations, by forming intelligible classes and those who do not have the right to a life worthy of protection by the State. State. In addition to social and symbolic inequalities and how the subject can reinvent itself through struggles and in a liquid and unequal world, in search of new ways of living, so that in the socio-economic and symbolic the socio-economic and symbolic spheres resistance and self-government. The aim of the article is to describe how people have legal rules that appear to be equal before the law. that, in practice, intolerance of race, gender and socio-economic inequalities, of the poor white man, for example, means that the rights of classes with less chance of winning power, such as the community, are minimized. of winning power, such as the LGBTQIA+ community. The relevance and importance of article goes beyond the socio-economic measurement of individuals and communicates with symbolic interactions of being and having, in the moral and ethical question of how the subject can govern themselves and others, even if they live in an unequal country like Brazil.
GÊNERO E SEXUALIDADE SOB A ANÁLISE ARQUEGENEÁLOGA DO SABER-PODER
Keywords: Governmentality; Knowledge-power; LGBTQIA+ community; Resistance